The Cytokinin Oxidase/Dehydrogenase CKX1 Is a Membrane-Bound Protein Requiring Homooligomerization in the Endoplasmic Reticulum for Its Cellular Activity. Issue 3 (4th January 2018) - Niemann, Michael C.E.; Weber, Henriette; Hluska, Tomá¡; Leonte, Georgeta; Anderson, Samantha M.; Novák, Ondřej; Senes, Alessandro; Werner, Tomá¡
Abstract : The Arabidopsis cytokinin oxidase/dehydrogenase CKX1 plays a key role in cytokinin degradation in the endoplasmic reticulum. Abstract: Degradation of the plant hormone cytokinin is controlled by cytokinin oxidase/dehydrogenase (CKX) enzymes. The molecular and cellular behavior of these proteins is still largely unknown. In this study, we show that CKX1 is a type II single-pass membrane protein that localizes predominantly to the endoplasmic reticulum (ER) in Arabidopsis ( Arabidopsis thaliana ). This indicates that this CKX isoform is a bona fide ER protein directly controlling the cytokinin, which triggers the signaling from the ER. By using various approaches, we demonstrate that CKX1 forms homodimers and homooligomers in vivo. The amino-terminal part of CKX1 was necessary and sufficient for the protein oligomerization as well as for targeting and retention in the ER. Moreover, we show that protein-protein interaction is largely facilitated by transmembrane helices and depends on a functional GxxxG-like interaction motif. Importantly, mutations rendering CKX1 monomeric interfere with its steady-state localization in the ER and cause a loss of the CKX1 biological activity by increasing its ER-associated degradation. Therefore, our study provides evidence that oligomerization is a crucial parameter regulating CKX1 biological activity and the cytokinin concentration in the ER. The work also lends strong support for the cytokinin signaling from the ER and for the functional relevance of the cytokinin pool in this compartment.